COVID-19 Experience: Taking the Right Steps at the Right Time to Prevent Avoidable Morbidity and Mortality in Nigeria and Other Nations of the World - Oleribe, Obinna O (Int J Gen Med, 2020)
The 2020 Coronavirus pandemic has caused countless governmental and societal challenges around the world. Nigeria, Africa’s most populous nation, has been exposed in recent years to a series of epidemics including Ebola and Lassa fever. In this paper, we document our perception of the national response to COVID-19 in Nigeria. The response to the pandemic is with a healthcare system that has changed as a result of previous infectious disease outbreaks but in the context of scarce resources typical of many low-middle income countries. We make recommendations regarding what measures should be in place for future epidemics.